2019
DOI: 10.1111/jvh.13205
|View full text |Cite
|
Sign up to set email alerts
|

Frequent delayed spontaneous seroclearance of hepatitis B virus after incident HBV infection among adult high‐risk groups

Abstract: High rates (~25%) of developing chronic hepatitis B virus (HBV) infection (hepatitis B surface antigen (HBsAg)‐positive for > 6 months following infection) have been observed in people who use drugs (PWUD) and men who have sex with men (MSM). We aimed to estimate the frequency of delayed HBsAg seroclearance, along with its determinants, and time to delayed HBsAg seroclearance. Data were used from MSM and PWUD enrolled in the Amsterdam Cohort Studies (1985‐2002) who had anti‐hepatitis B core antibody seroconver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Some other studies appealed opposite findings. For instance a Hong Kong study of 4,568 cohort members and a research of 148 cohort members in Netherlands also found middle-age was associated with developing chronic infection and low HBsAg seroclearance rate compared with aging people ( 25 , 26 ). The confusing result has not been explained clearly and could partly be due to the increasingly complex innate and adaptive immune responses in elder people ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies appealed opposite findings. For instance a Hong Kong study of 4,568 cohort members and a research of 148 cohort members in Netherlands also found middle-age was associated with developing chronic infection and low HBsAg seroclearance rate compared with aging people ( 25 , 26 ). The confusing result has not been explained clearly and could partly be due to the increasingly complex innate and adaptive immune responses in elder people ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our survey showed that the incidence rate of new hepatitis B infection for males was significantly higher than that for females (684.88 vs. 536.68 per 100,000 person-years, p < 0.001), and 31-40, 41-50, 51-60 age groups had lower new infection rate than younger and elder age groups (Table 1). The phenomenon that males were more likely to have been infected with HBV than females reported by many previous studies could mainly be explained by behavioral differences (11,(21)(22)(23)(24)(25)(26)(27). In this research it may relate to the relatively conservative ideology in this county.…”
Section: Discussionmentioning
confidence: 47%